Non-plug technique of bilayer patch device insertion for indirect inguinal hernia repair - Ilić, Miroslav; Putnik, Srdjan; Kuhajda, Ivan; Ivanov, Dejan (Vojnosanitetski pregled, 2017)
Background/Aim. Despite a huge success in decrease rate of recurrences of inguinal hernia in mesh and “plug in” techniques, a new problem appears such as chronic pain and other complications. The aim of this paper was to present the original modification of bilayer patch device (Prolene Hernia System®, Ethicon) insertion in “non-plugged” fashion and 11-year experience with this open technique for the indirect hernia repair in a male. Methods. This retrospective study included 96 male patients with 103 indirect unilateral and bilateral inguinal hernias, operated due to a primary or recurrent hernia in an 11-year interval (2004–2015). In all operation an extended Prolene Hernia System® (PHS) bilayer patch device was inserted medially of inferior epigastric vessels through a small incision in Hasselbach’s triangle, thus avoiding plug component of device connector into the internal ring. All data were taken from the medical records, operative protocols, and telephone questionnaire. Results. Non-plugged technique of bilayer patch device insertion was presented in details. Mean age of patients was 59 years. There were 3 (2.91%) patients with procedure-related complications, two patients with postoperative seroma and one with scrotal ecchymosis. There were 86 (89.6%) patients who answered on the questionnaire. During 11 years of following, recurrence of a hernia occurred in 1 patient, one had funiculocele and only one had chronic pain during 6 months. Almost all patients (97.68%) were satisfied with the procedure and results of hernia surgery. Conclusion. Non-plugged insertion of bilayer patch device is a safe technique for solving the primary and recurrent indirect inguinal hernias. The low incidence of the recurrence and chronic pain many years after the operation justifies this technique even in hospitals not specialized for the hernioplasty.